2018
DOI: 10.3390/en11071702
|View full text |Cite
|
Sign up to set email alerts
|

Feature Extraction and Comprehension of Partial Discharge Characteristics in Transformer Oil from Rated AC Frequency to Very Low Frequency

Abstract: The reactive current can be reduced effectively by decreasing the frequency of the voltage in partial discharge (PD) test, especially for equipment with large capacitance. Thus, the cost and volume of the test power supply can be economized. To figure out the difference of PD characteristics in transformer oil between rated alternating-current (AC) frequency (50 Hz) and low frequency, tests are conducted from rated AC frequency to very low frequency (0.1 Hz) based on impulse current method. The results show th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…PD feature extraction is an important step in insulation fault diagnosis. The common methods include statistical atlas (SA) [2], wave analysis (WA) [3] and wavelet transform (WT) [4]. However, SA has the limitations of high request of sampling rate, large data size and slow speed of data processing which are not suitable for on-line monitoring.…”
Section: Introductionmentioning
confidence: 99%
“…PD feature extraction is an important step in insulation fault diagnosis. The common methods include statistical atlas (SA) [2], wave analysis (WA) [3] and wavelet transform (WT) [4]. However, SA has the limitations of high request of sampling rate, large data size and slow speed of data processing which are not suitable for on-line monitoring.…”
Section: Introductionmentioning
confidence: 99%
“…The discharge of suspended and mobile particles was simulated and experimentally studied by Tang et al . and Zhou . They found that the deformation of microbubbles causes the electric field distortion and discharge.…”
Section: Introductionmentioning
confidence: 99%